Enhancing the capability of posyandu cadres as an effort to improve toddler weight through tuina massage - Sofiana, Juni; Indriyastuti, Hastin Ika; Prabandari, Fitria (Community Empowerment, 2025)
Toddlerhood is a critical period for the development of feeding difficulties, which can have negative impacts on young children. These effects not only affect their health but also influence their daily activities and overall growth and development. The consequences of feeding difficulties can include weight loss, potentially leading to malnutrition and stunting. The objective of this community service initiative was to enhance the knowledge and skills of cadres at integrated health posts (Posyandu) in Tuina massage as a strategy to improve the weight of toddlers. The method employed in this activity involved providing education and practical training in Tuina massage to health cadres within the working area of the Puring Community Health Center. The results of this community service project demonstrated significant differences between pre- and post-evaluation scores, in both knowledge and skill domains. Following the intervention, 90.5% of cadres exhibited good knowledge regarding Tuina massage, and 71.4% were able to competently perform the technique.